2017
DOI: 10.21608/ejoh.2017.1712.1020
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Growth of Sanchezia Plant by Foliar Application of Micronutrients and Paclobutrazol

Abstract: APOT EXPERIMENT was carried out to evaluate the effect of foliar application of micronutrients mixtures and paclobutrazol on controlling growth of sanchezia plants. The experimental treatments were laid out in a split plot arrangement using a randomized complete block design. Micronutrients mixtures of Zn + Mn + Fe+ B at 50 (C 1 ), 100 (C 2 ) and 150 (C 3 ) ppm of each element were assigned to main plot, while paclobutrazoltreatments; 8, 16, and 24 mgL -1 were allocate to sup-plot. Spraying plants with tap wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Besides, Zamani et al, (2016) indicated that spraying the foliage of rosemary and thuja "Morgan" plants with PP-333 at 1000 and 4000 ppm concentrations increased proline, chlorophyll a and b and total chlorophyll (a + b) content more than control plants. Also, foliar application of PP-333 at 16 mg/l markedly increased total carbohydrates and mineral contents in the leaves of Sanchezia nobilis plants (Heikal, 2017).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Besides, Zamani et al, (2016) indicated that spraying the foliage of rosemary and thuja "Morgan" plants with PP-333 at 1000 and 4000 ppm concentrations increased proline, chlorophyll a and b and total chlorophyll (a + b) content more than control plants. Also, foliar application of PP-333 at 16 mg/l markedly increased total carbohydrates and mineral contents in the leaves of Sanchezia nobilis plants (Heikal, 2017).…”
Section: Discussionmentioning
confidence: 90%
“…On other ornamentals, many reports were decided by Auda et al, (2002) on Barleria cristata, Barett et al, (2003) on Petunia hybrida and Catharanthus roseus, Shahin et al, (2006) on Rudbeckia hirta, ( 95 ) Mahmoud et al, (2008) on Nerium oleander, Asgarian et al, (2013) on Zinnia, Shahin et al, (2014) on Chrysanthemum carinatum, Noor El-Deen et al, on Gaillardia pulchella, Abou-Dahab et al, (2015) on Russelia equisetiformis, Narayan (2015) on Tagetes erecta, El-Sadek (2016) on Hibiscus rosa-sinensis cv. Yellow, Zamani et al, (2016) on rosemary and Thuja "Morgan" Heikal (2017) on Sanchezia nobilis, Mohammed et al, (2017) on Lagerstroemia indica, Deniz and Omer Faruk (2018) on Fuchsia, Tawila (2018) on Celosia cristata, Naine et al, (2019) on ornamental pepper, Dong et al, (2020) on Paeonia lactiflora, Noor El-Deen (2020) on Ruellia simplex, Shahin and Moustafa (2021) on Althaea rosea and Noor El-Deen and Abou Elghait (2022) on Hibiscus rosasinensis cv. Cooperi.…”
Section: Introductionmentioning
confidence: 99%